The plane tree and the singing cicadas in Plato’s Phaedrus: the environment of dialogue - Guimarães, Henrique (Revista Archai, 2023)
This article aims to rethink the meaning of “nature” and the human in Plato, more specifically through some examples contained in the Phaedrus, a rare dialogue “further away” from the city. Phaedrus and Socrates leave Athens on a trail outside the walls, past the Ilisos stream and the breeze of the woods, and end up sitting in the shadows of trees full of singing cicadas. Is it possible to learn from oak trees or insects? The philosophy of this dialogue passes through the coolness of the shadows of the trees in the hot summer noon. This sensuous topography through the text reveals the writer Plato aware of the immersive meaning of the living drama between Phaedrus and Socrates. I draw attention to the participation-audience of natural elements, trees and cicadas in the dialogue between Phaedrus and Socrates, noting a care with the surrounding atmosphere, a special concern of Socrates in his palinode and in his final prayer to Pan. More than distinct and removed from nature, we rethink the human being (and reason) immersed in it – in an attempt to integrate a mythological and dialogical search between river, rock, plants, animals, humans, gods and demigods. The image of an overly rationalist and humanist Plato finds in this text a perspective of an inspired writer, a hybrid poet and philosopher, with a mission to restore language and the city to animal and cosmic life.